André Lhote and the painting “Interior com figuras femininas” (1936) of the MASP collection - Gonçalves, Bárbara; Zacarias, Gabriel (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
André Lhote (France, 1885 - 1962) was a sculptor, painter, critic and educator. He wrote critical texts, books and articles on aspects of vanguard production and treatises on landscape and figure. Two of his paintings are present in the collection of the "Museu de Arte de São Paulo Assis Chateaubriand" (MASP). Both entered the museum collection in the second half of the 1940s, a period that coincided with the beginnings of its foundation and the elaboration of its pedagogical objective. This work proposes the study of one of these paintings, "Interior com figuras femininas", of 1936, concerning its thematic, pictorial, contextual and market aspects. In this way, it was possible to unveil characteristics and tendencies of his painting, in the dialogues he establishes with artistic movements and in the originality of his works.